Financial Literacy, FinTech, Social Capital, and Locus of Control as Determinants of MSME Financial Inclusion in Surabaya - Davin Windiarta; Condro Widodo (Universitas Muhammadiyah Semarang, 2026)
This study aims to analyze the influence of financial literacy, financial technology, social capital, and locus of control on financial inclusion in MSME players in Rungkut Sub-district, Surabaya City. The background of this research is the importance of financial inclusion in supporting the economic growth of MSMEs, and there remain obstacles such as low financial literacy, limited fintech adoption, weak social capital, and an unoptimal locus of control. This research uses a quantitative approach with a random sampling technique. Data were collected via questionnaires and analyzed using PLS-SEM with SmartPLS. The results showed that financial literacy and social capital have a positive and significant effect on financial inclusion. In contrast, financial technology and locus of control have no significant effect. The findings imply that improving financial literacy and strengthening social networks are key to promoting financial inclusion for MSMEs. This research is expected to serve as a reference for policy-making and empowerment programs for MSMEs, grounded in literacy and social development.